HLA-Matched Donor-Recipient Combinations and Kidney Transplant Probabilities in a Specific Colombian Population (2016)
Introduction: In Colombia, despite the fact that kidney transplants are the most common type of transplant surgery, a great number of transplanted patients do not achieve the desired Human Leucocyte Antigen (hla) compatibility. hla compatibility plays an important role in graft survival; patients with matched-hla have a lower chance of graft-versus-host disease and graft ejection. Objective: To determine the probability of finding an hla-matched donor-recipient pairs according to hla−a, −b and −drb1 frequencies in a specific Colombian population. Materials and methods: The study included a total of 484 unrelated individuals (61 donors and 423 recipients) from the hla registry. hla alleles were determined by polymerase chain reaction sequence with specific indicators. Results: hla–A*02, –A*24, –B*35 and –DRB1*04 alleles showed the highest minimum allele frequency (>10%). In addition, hla–A*24–B*35–DRB1*04 was the most frequent extended haplotype in both donors and recipients (7.38 % and 6.76 %, respectively). Our experimental evidenceshowed that the maximum chance of finding at least one hla allele-matched kidney is 20.3 % for a patient with the most frequent extended haplotype, whereas for patients with rare or non-common haplotypes this probability is rather unlikely. Discussion: In terms of probability, the chance of finding an hla matched kidney donor/recipients in our region is low. This is due, at least in part, to the higher number of alleles and a the lower donation rate. Therefore, to define the hla profile of a population is important for establishing transplantation programs and alternative strategies in the kidney donation and allocation processes.